Prevalência de retinopatia da prematuridade em RN atendidos na Fundação Hospital de Clínicas Gaspar Vianna de novembro de 2004 a novembro de 2008 - MARQUES, Mara Pureza (2023)
Objective: To analyze the prevalence of retinopathy of prematurity in newborns attended in public service Fundação Hospital de Clínicas Gaspar Vianna (FHCGV) in the period November 2004 to November 2008. Methods: A retrospective, descriptive cross-sectional type of all newborns attended in the Intensive Care Unit Neonatal of FHCGV with birthweight of 2000g or less and / or gestational age less than 37 weeks from November 2004 to November 2008. During the study period, 452 infants were seen, among which 138 had a diagnosis of ROP, and it is the sample of the study. Results: The prevalence of ROP among those assessed was 45.70% (138), of these, 55.8% (77) infants had birthweight greater than 1500 and 47.83% had gestational age above 32 weeks; 9.42% of infants with ROP required surgical treatment. Conclusion: The FHCGV, responsible for the care program for the prevention of ROP in the Belém city, had a high prevalence of ROP in infants with birthweight and gestational age above the national and international criteria. Thus the criteria for prevention of blindness by the ROP must be based on individual characteristics of each country or even regions within a country. It is hoped that with better knowing the size of ROP in each region is possible to establish strategies for prevention and treatment.